1979
DOI: 10.1002/bip.1979.360180417
|View full text |Cite
|
Sign up to set email alerts
|

Co‐oligopeptides containing two aromatic residues spaced by glycyl residues. X. Proton magnetic resonance study of co‐oligopeptides of tryptophan and glycine

Abstract: SynopsisThe 'H-nmr spectra of co-oligopeptides of tryptophan and glycine with structure H-GlyTrp-(Gly),-Trp-Gly-OH (n = 0-2) and those of several di-and tripeptides have been recorded a t 360 MHz with CDBOD solutions containing 0.1N NaOD. The assignment of resonance signals was generally possible by comparing the spectra of structurally related peptides with each other. In order to solve the remaining ambiguities in the assignment, H-(cuL,BS)(cu,@-dz)Trp-OH, H-Trp-((~L,BS)(cu,P-ds)Trp-0H, and H -T r p -( 6 1 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…This assignment was consistent with the data proposed by Petrich et al 39 although the population ratio of rotamers was slightly incompatible, and the ratio obtained by our data was also inconsistent with the one obtained by NMR. 17 These discrepancies might be due to solvent condition, and the fraction of rotamers proposed here is not one in the ground-state but the fluorescence fraction which depends on optical parameters and quantum yields of each rotamer. In this study, any trace indicating conformational exchange between rotamers was not observed.…”
Section: Resultsmentioning
confidence: 95%
“…This assignment was consistent with the data proposed by Petrich et al 39 although the population ratio of rotamers was slightly incompatible, and the ratio obtained by our data was also inconsistent with the one obtained by NMR. 17 These discrepancies might be due to solvent condition, and the fraction of rotamers proposed here is not one in the ground-state but the fluorescence fraction which depends on optical parameters and quantum yields of each rotamer. In this study, any trace indicating conformational exchange between rotamers was not observed.…”
Section: Resultsmentioning
confidence: 95%
“…For example, Oba and coworkers were able to obtain a N α -acylated dehydrotryptophan 1.24 in good yield (Scheme 1.10); whereas, in earlier work, yields of 20% and 26% were obtained by Kirby et al and Skrabl et al respectively in the synthesis of a very similar indole-N-protected acyl-dehydrotryptophan 1.26 (Scheme 1.11). [35][36][37] In both scenarios, the Z-dehydrotryptophan was formed exclusively.…”
Section: Dehydrotryptophan Derivatives Using the Erlenmeyer Synthesismentioning
confidence: 98%
“…Each conformation has a different microenvironment, yielding to a distinct nonradiative decay rate due to a different proximity and orientation to quencher groups (Szabo and Rayner, 1980;Petrich et al, 1983). The existence of stable Trp rotamers has been observed by NMR (Skrabal et al, 1979;Dezube et al, 1981). The fluorescence decay of individual Trp rotamers in supersonic jets is monoexponential (Phillips et al, 1988).…”
Section: Lifetime Assignmentmentioning
confidence: 99%